Protein redistribution from skeletal muscle to splanchnic tissue on fasting and refeeding in young and older healthy individuals - Moreau, Karine; Walrand, Stéphane; Boirie, Yves (Journal of the American Medical Directors Association, 2013)
During aging, a shift of protein metabolism from muscle to splanchnic tissue contributes to increased muscle protein loss after a period of metabolic stress (eg, fasting). To study the adaptation of protein metabolism in the whole body and tissue (ie, skeletal muscle and splanchnic area) to metabolic stress, such as short-term fasting and refeeding, in aged people. We studied splanchnic and muscle protein metabolism after 38 hours of fasting and refeeding in 7 young (5 men/2 women, 24.4 ± 2.0 years) and 8 elderly individuals (6 men/2 women, 70.6 ± 3.1 years). We used intravenous (IV) L-[(13)C6]phenylalanine, IV L-[(2)H3]leucine, and oral L-[(13)C1]leucine to obtain (1) whole-body protein kinetics, (2) muscle and albumin fractional synthesis rate (FSR, %/d; (13)C6-Phe, and (13)C1-Leu), and (3) splanchnic extraction during fasting and refeeding (%, (2)H3- and (13)C1-Leu). Whole-body protein breakdown was activated during fasting in young and older individuals (P < .01 vs fasted state). Muscle FSR remained unchanged in both groups and not stimulated by refeeding in either group with either IV (13)C Phe or oral (13)C Leu, probably because of high plasma levels of essential amino acids (EAAs) and branched-chain amino acids (BCAAs). Splanchnic extraction of leucine was 42% higher in the elderly individuals (P = .03 vs young) and was associated with an increased albumin synthesis rate in elderly individuals in the fed state (P < .05 vs young). Splanchnic protein metabolism is modified by age, but this metabolic change is not associated with a lower synthesis rate of muscle protein, provided high plasma levels of essential EAAs are maintained. Our data also suggest that splanchnic protein synthesis is a metabolic priority during recovery after metabolic stress in healthy elderly persons and that it might be even more affected in polymedicated older individuals having chronic diseases.